(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Even with an innovative proposition in the history of theater as form and content, Bertolt Brecht’s epic-dialectical theater (1967; 1978) did not deeply consider the gender perspective in its conception, since class struggle is the central debate of this theory. However, feminist thinkers such as Elin Diamond (2011) and Della Pollock (1989) enable a broader understanding of the theory by placing genre as an allied category in the pursuit of revolutionary theater. The first author makes a reading of the “method” of dialectic epic theater and the second brings some considerations about the female characters of Brecht’s dramaturgy.